Atypical nested 22q11.2 duplications between LCR22B and LCR22D are associated with neurodevelopmental phenotypes including autism spectrum disorder with incomplete penetrance. Issue 2 (4th January 2019) - Woodward, Karen J.; Stampalia, Julie; Vanyai, Hannah; Rijhumal, Hashika; Potts, Kim; Taylor, Fiona; Peverall, Joanne; Grumball, Tanya; Sivamoorthy, Soruba; Alinejad‐Rokny, Hamid; Wray, John; Whitehouse, Andrew; et al.
Abstract: Background: Chromosome 22q11.2 is susceptible to genomic rearrangements and the most frequently reported involve deletions and duplications between low copy repeats LCR22A to LCR22D. Atypical nested deletions and duplications are rarer and can provide a valuable opportunity to investigate the dosage effects of a smaller subset of genes within the 22q11.2 genomic disorder region. Methods: We describe thirteen individuals from six families, each with atypical nested duplications within the central 22q11.2 region between LCR22B and LCR22D. We then compared the molecular and clinical data for patients from this study and the few reported atypical duplication cases, to the cases with larger typical duplications between LCR22A and LCR22D. Further, we analyzed genes with the nested region to identify candidates highly enriched in human brain tissues. Results: We observed that atypical nested duplications are heterogeneous in size, often familial, and associated with incomplete penetrance and highly variable clinical expressivity. We found that the nested atypical duplications are a possible risk factor for neurodevelopmental phenotypes, particularly for autism spectrum disorder (ASD), speech and language delay, and behavioral abnormalities. In addition, we analyzed genes within the nested region between LCR22B and LCR22D to identify nine genes ( ZNF74, KLHL22, MED15, PI4KA, SERPIND1, CRKL, AIFM3, SLC7A4, and BCRP2) with enriched expression in the nervous system, each with unique spatiotemporal patterns in fetal and adult brain tissues. Interestingly, PI4KA is prominently expressed in the brain, and this gene is included either partially or completely in all of our subjects. Conclusion: Our findings confirm variable expressivity and incomplete penetrance for atypical nested 22q11.2 duplications and identify genes such as PI4KA to be directly relevant to brain development and disorder. We conclude that further work is needed to elucidate the basis of variable neurodevelopmental phenotypes and to exclude the presence of a second disorder. Our findings contribute to the genotype–phenotype data for atypical nested 22q11.2 duplications, with implications for genetic counseling. Abstract : In this study, we describe thirteen individuals from six families, each with atypical nested duplications within the region between LCR22B to LCR22D. We report that such duplications represent a risk factor for neurodevelopmental traits including autism spectrum disorder, and identify genes such as PI4KA which could underlie such phenotypic traits.